2022
DOI: 10.3389/fphys.2022.909372
|View full text |Cite
|
Sign up to set email alerts
|

Training machine learning models with synthetic data improves the prediction of ventricular origin in outflow tract ventricular arrhythmias

Abstract: In order to determine the site of origin (SOO) in outflow tract ventricular arrhythmias (OTVAs) before an ablation procedure, several algorithms based on manual identification of electrocardiogram (ECG) features, have been developed. However, the reported accuracy decreases when tested with different datasets. Machine learning algorithms can automatize the process and improve generalization, but their performance is hampered by the lack of large enough OTVA databases. We propose the use of detailed electrophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…In pursuit of developing methodologies to study physical systems, the scientific community has consistently relied on examining realistic models. To gain a deeper understanding of physical systems and advance methodologies through data-driven approaches, the data itself need not be confined to these physically realistic models. This realization unveils a new avenue for data generation, as synthetic systems are not bound by the same limitations as their physical counterparts. In this article, we demonstrate the generation of synthetic data and its subsequent utilization in studying physically relevant systems through the implementation of ML models.…”
Section: Discussionmentioning
confidence: 99%
“…In pursuit of developing methodologies to study physical systems, the scientific community has consistently relied on examining realistic models. To gain a deeper understanding of physical systems and advance methodologies through data-driven approaches, the data itself need not be confined to these physically realistic models. This realization unveils a new avenue for data generation, as synthetic systems are not bound by the same limitations as their physical counterparts. In this article, we demonstrate the generation of synthetic data and its subsequent utilization in studying physically relevant systems through the implementation of ML models.…”
Section: Discussionmentioning
confidence: 99%
“…We originally expected that transfer learning techniques would need to be applied. In a work published after the completion of out study, the authors also found simulated data to be at least beneficial for the performance on clinical data [12]. If clinical data was available in a larger quantity, as it was to the authors of [12], results could have further improved by using a part of the clinical data as training data, incorporated into the training process.…”
Section: Discussionmentioning
confidence: 99%
“…In a work published after the completion of out study, the authors also found simulated data to be at least beneficial for the performance on clinical data [12]. If clinical data was available in a larger quantity, as it was to the authors of [12], results could have further improved by using a part of the clinical data as training data, incorporated into the training process. Unfortunately at the current state, localization errors obtained from our implemented methods could be as high as 110 mm on clinical data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, synthetic images were generated to train neural networks to track cardiac motion and calculate cardiac strain ( Loecher et al, 2021 ), estimate tensors from free-breathing cardiac diffusion tensor imaging ( Weine et al, 2022 ), and predict end-diastole volume, end-systole volume, and ejection fraction ( Gheorghita et al, 2022 ). Furthermore, synthetic photoplethysmography (PPG) signals were generated to detect bradycardia and tachycardia ( Sološenko et al, 2022 ), and synthetic electrocardiogram (ECG) signals were generated to detect r-waves during different physical activities and atrial fibrillation ( Kaisti et al, 2023 ), and to predict the ventricular origin in outflow tract ventricular arrhythmias ( Doste et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%